A survey of Australian dairy farmers’ attitudes to their business, its challenges and transitioning to alternative enterprises - Celik, Esra; Bogueva, Diana; Phillips, Clive J.C.; Marinova, Dora (Nature Publishing Group, 2025)
Dairy farmers are grappling with serious business challenges, including rising operational costs, labour shortages, unstable milk prices, changing consumer preferences, long hours with minimal downtime and unstable weather patterns due to climate change impacts. Using a telephone-based representative survey and interviews with 147 Australian dairy farmers conducted in 2023, we employed a mixed-method approach combining quantitative and qualitative analysis to determine the challenges and primary concerns of the participants, as well as to explore potential solutions. Four key variables that contributed significantly to a binary logistic regression model of transition intentions were identified, namely: level of satisfaction with dairy farming, openness to exploring other agricultural alternatives to dairy farming, preference to receive financial and/or other support to remain in the industry and preference to receive financial and/or other support to transition into a different form of farming or business. This model accurately predicted the probability that farmers were considering transitioning away from dairy farming and the probability that they were considering staying in dairy farming. This deepens our understanding of the challenges faced by farmers in the Australian dairy industry, and provides policymakers, industry stakeholders and researchers with critical insights to facilitate transition pathways that will enhance farmers’ future sustainability.